Epigenetic therapy of cancer : Preclinical models and treatment approaches - Jones, Peter A.; Lubbert, Michael (Springer Berlin Heidelberg, 2014)
The growing knowledge about disturbances of epigenetic gene regulation in hematopoietic stem cell disorders such as myeloid leukemias and preleukemias (myelodysplasias) is now being translated into treatment approaches that target the epigenetic defects pharmacologically. Such approaches include reactivation of tumor suppressor genes and other antiproliferative genes by reversal of DNA hypermethylation through azanucleosides, and use of HDAC inhibitors to reverse gene silencing mediated by chimeric, leukemia-specific transcription factors. This book first presents the latest evidence derived from preclinical models regarding the epigenetic regulation of hematopoietic stem cell differentiation and hemoglobin production. The significance of DNA methylation abnormalities in hematopoietic disorders and of epigenetic disturbances in lung cancer and other solid tumors is then discussed. A major part of the book, however, relates specifically to the translation of basic research and drug development to clinical applications, and in this context both present and future clinical strategies are considered. Individual chapters are devoted to the use of DNA hypomethylating agents and chromatin-modifying agents, and the treatment of hematologic malignancies and solid tumors by means of epigenetic agents is discussed in detail.